Micronized Palmitoylethanolamide, Hempseed Oil, and Maritime Pine Bark Dry Extract (Pelvipea®) for Pelvic Pain: An In Vitro Study for Urothelial Inflammation Treatment - Alessandro Tafuri; Andrea Panunzio; Rita De Mitri; Federico Benetti; Elisa Gaio; Vincenzo Pagliarulo (Cells, 2023)
Urothelial inflammation plays a key role in the pathogenesis of chronic pelvic pain due to its origin in the bladder. The aim of this study was to evaluate the efficacy of a patent-pending formulation (Pelvipea®) composed of micronized palmitoylethanolamide (PEA), hempseed oil, and maritime pine bark dry extract in reducing urothelial inflammation, as well as the effect of each ingredient individually, in order to define the synergistic effect of the three ingredients. An in vitro bladder urothelium model composed of the T24 cell line was exposed to a conditioned media obtained by treating macrophage-differentiated THP-1 cells with different concentrations of the functional ingredients and a mixture of them in the presence of the pro-inflammatory stimulus of Escherichia coli. Cells exposed only to the inflammatory stimulus in the absence of pre-treatment were considered as a positive control for inflammation. The impact of each functional ingredient and their mixture on inflammation was evaluated by the determination of transcription factor NF-kB and of pro-inflammatory cytokine expression. Statistical analysis was performed using the t-test, comparing the mixture and the single ingredients for every condition tested. All results were reported as fold change (mean ± standard deviation), the ratio between the values obtained from the respective treatments for inflammation control. The three functional ingredients did not induce negative effects on THP-1 cell vitality. The levels of NF-kB were reduced following treatment with hempseed oil, maritime pine bark dry extract, and the mixture at all tested concentrations, and with micronized PEA from 25 to 200 μg/mL. Treatment with the mixture resulted in the lowest expression levels of interleukins (IL)-1β, IL-6, and IL-8 compared to the single functional ingredients at a concentration of 230 μg/mL, with values of 0.08 (±0.00), 0.01 (±0.00), and 0.32 (±0.01), respectively. The mixture of micronized PEA, hempseed oil, and maritime pine bark dry extract (Pelvipea®) at 230 μg/mL showed the best efficacy in urothelial IL-1β, IL-6, and IL-8 reduction compared with the singular components. This formulation may represent a promising therapeutic option to relieve painful symptoms originating in the bladder. However, in vivo studies are needed to confirm these results.